Movimentos de mudança: um estudo de caso sobre inovação curricular em cursos de Licenciatura da UFPR Litoral - Franco, Elize Keller (2014)
The recurrent complaint that the preparation offered in initial training courses are not offered appropriate responses to the new demands of teachers' work in contemporary society and the challenges faced by teachers in their daily practices have raised doubts about the revision of curricula that prepares these professionals . In this context, this study aims at a critical analysis of an alternative curriculum organization that has been developed in the courses of initial teacher development, specifically in the courses Science Undergraduate, Art & Language and Communication of Federal University of Parana - Coastline campus. For this, we chose the guiding question as in what extent the proposal being developed in UFPR Coastline brings elements with potential to contribute to a new curricular paradigm in initial teacher development. The adopted methodological approach for this study is the qualitative research approach in the form of case study. To obtain the data, we focused on document analysis and discussion groups with students and teachers. Authors such as Garcia (1999 ) , Tardif (2011 ) , Masetto ( 2003, 2006 , 2007, 2009 , 2012) , Gatti (2010 ) , André ( 2005, 2009 , 2010) , Diniz - Pereira ( 2007, 2010 ) , Romanowski ( 2010, 2012 ) , Imbernon (2009 ) , Saviani ( 2005, 2009 ) , Tanuri (2000 ) , Carbonell (2002 ) , Silva (2007 ) , Moreira (2006 ) , Lopes and Macedo (2011 ) supported the construction of the theoretical framework concept that guided the research from theirs theories on innovation , teacher formation and curriculum. The data indicate that the curriculum reform in progress manifests with characteristic movements of change with innovation in a set of core and relevant elements such as design and curriculum organization , teaching knowledge , models of formation , practical activities / stage and methodological principles. The character of building in movement of the curriculum, open to the collective intelligence of educators in their institutional contexts find room for diversification and innovation, confronts us with the possibility of a new paradigm in process. Thus, this research contributes to the field of curriculum theory and practice analysis to bring an experience that puts into action directions that have long putting to the curricula in initial teacher development